2016
DOI: 10.1124/jpet.116.235689
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular Unbound Atorvastatin Concentrations in the Presence of Metabolism and Transport

Abstract: Accurate prediction of drug target activity and rational dosing regimen design require knowledge of drug concentrations at the target. It is important to understand the impact of processes such as membrane permeability, partitioning, and active transport on intracellular drug concentrations. The present study aimed to predict intracellular unbound atorvastatin concentrations and characterize the effect of enzyme-transporter interplay on these concentrations. Single-pass liver perfusion studies were conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…To compare the passive rate constants to the values found in the literature for atorvastatin, the passive rate constants (k fA and k bA ) were scaled from Model 2 to clearances (P dif and P def ) respectively by multiplying by the relevant volume. P dif was 11-fold greater than P def (0.55 [0.1-11.7] and 0.051 [0.03-0.2] ml/min/1 Â 10 6 cells respectively), possibly due to intracellular binding of atorvastatin (Kulkarni et al, 2016;Paine et al, 2008;Yabe et al, 2011). P dif for atorvastatin was minor (<1%) compared to the transporter mediated uptake clearance (CL up ¼ 3375 [2722-10750] ml/min/1 Â 10 6 cells, Equation (11)), therefore even though the range of values on k fA and thus P dif estimation were large it is of little consequence in the uptake of atorvastatin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To compare the passive rate constants to the values found in the literature for atorvastatin, the passive rate constants (k fA and k bA ) were scaled from Model 2 to clearances (P dif and P def ) respectively by multiplying by the relevant volume. P dif was 11-fold greater than P def (0.55 [0.1-11.7] and 0.051 [0.03-0.2] ml/min/1 Â 10 6 cells respectively), possibly due to intracellular binding of atorvastatin (Kulkarni et al, 2016;Paine et al, 2008;Yabe et al, 2011). P dif for atorvastatin was minor (<1%) compared to the transporter mediated uptake clearance (CL up ¼ 3375 [2722-10750] ml/min/1 Â 10 6 cells, Equation (11)), therefore even though the range of values on k fA and thus P dif estimation were large it is of little consequence in the uptake of atorvastatin.…”
Section: Discussionmentioning
confidence: 97%
“…Atorvastatin is an HMG-CoA reductase inhibitor used to treat hypercholesterolaemia, and is the third most prescribed drug in the USA (Fuentes et al, 2018). Atorvastatin is taken up into hepatocytes with; 96%-98% of the uptake as carrier mediated in rat hepatocytes, high intracellular binding (fraction unbound ¼ 0.011-0.015; Kulkarni et al, 2016;Paine et al, 2008;Yabe et al, 2011), and metabolism through rCyp3a into ortho or para substituted hydroxylated metabolites (Lau et al, 2006;Watanabe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the strong influence of active uptake on the kinetics of ATO, the extracellular plasma concentration is actually lower than the hepatic intracellular concentration for ATO. It was reported that the predicted unbound intracellular ATO concentration was 5.14 μM obtained from single-pass liver perfusion experiments, which would be five-to 18fold higher than the extracellular plasma concentration (Kulkarni, Korzekwa, & Nagar, 2016;Paine, Parker, Gardiner, Webborn, & Riley, 2008). Meanwhile, C max at the maximum tolerated dose is a pharmacodynamic concentration rather than a toxic or toxicological concentration.…”
Section: Discussionmentioning
confidence: 98%
“…We have successfully modeled membrane partitioning and diffusion into and out of cells using an explicit membrane-modeling approach. 75,76 This suggests that in addition to membrane partitioning, permeability data could be utilized to model parent and metabolite distribution. Efforts to incorporate the TDI models presented here into a physiological framework are currently underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%